IN SILICO STUDY : HERMETIA ILLUCENS BASED ACUTE RESPIRATORY INFECTION TREATMENT - Agsari, Sintia Intan Agsari; Alzaini Bychaqi, Imam Ali; Tri Wibowo, Bintang Aditia (JARES (Journal of Academic Research and Sciences), 2024)
The novel coronavirus is now referred to as severe and critical acute respiratory syndrome coronavirus-2 (SARS-CoV-2). There have been few studies about SARS-CoV-2 co-infection may significantly inhibit the immune system of host, increase antibacterial therapy intolerance, and be harmful to the prognosis of the disease. The highest co infection comes from Streptococcus pneumoniae. Bacterial co-infection in the setting of viral pneumonia is known as major cause of mortality. Therefore, therapeutics such as antibiotics are needed to be able to kill and inhibit these bacteria. In this connection, the inaccurate use of antibiotics causes multi-drug resistant and worsens their immature immune systems. Hermetia illucens contains AMPs and various amino acids that synergistically have the potential to overcome this problem. Research on the use of crude maggot extract as a candidate for acute respiratory infection treatment products is still not available and has never been reported. This study aims to conduct in silico computerized tests related to the potential of maggot extract as antibacterial and anti-inflammatory properties, analyze its interaction with target proteins, bioavailability and ligand toxicity in maggot extract, and docking analysis of ligand-receptor. The results showed that the maggot extract had activity as peptidoglycan glycosyltransferase inhibitor, antibacterial, and anti-inflammatory. A binding affinity of the maggot AMPs ligands (defensin, diptericin, and attacin) to MurC receptor protein Streptococcus pneumoniae is also found. The antibacterial and anti-inflammatory abilities of bioactive maggots have the potential for used as a candidate treatment products for SARS-CoV-2 co-infection with Streptococcus pneumoniae as a biomedical innovation.